2011
DOI: 10.1002/jez.719
|View full text |Cite
|
Sign up to set email alerts
|

How do hatcheries influence embryonic development of sea turtle eggs? Experimental analysis and isolation of microorganisms in leatherback turtle eggs

Abstract: Many conservation programs consider translocation of turtle nests to hatcheries as a useful technique. The repeated use of the same incubation substrate over several seasons in these hatcheries could, however, be harmful to embryos if pathogens were able to accumulate or if the physical and chemical characteristics of the incubation environment were altered. However, this hypothesis has yet to be tested. We conducted two field experiments to evaluate the effects of hatchery sand and eggshell decay on the embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
2
17
0
1
Order By: Relevance
“…These microorganisms are usually saprobes but can invade living tissue under favorable conditions, and studies have reported that some of these fungi species infects sea turtle eggs and cause embryo mortality. Patino-Martinez et al (2012) reported similar results in the eggs of the sea turtle Dermochelys coreacea in Colombia, where F. solani and F. oxysporum were identified by phylogenetic analyzes; these fungi were possibly affecting the phenotype of the hatchling (body size). The first way of contamination of the eggs by Fusarium species probably occur through the secretion present in the oviduct, as suggested by Phillot et al (2002), likewise it might be the reason for fungi contamination in nests of other species that belong to Cheloniidae family, since several species of fungi have been isolated from the cloaca of females during breeding.…”
Section: Resultssupporting
confidence: 55%
“…These microorganisms are usually saprobes but can invade living tissue under favorable conditions, and studies have reported that some of these fungi species infects sea turtle eggs and cause embryo mortality. Patino-Martinez et al (2012) reported similar results in the eggs of the sea turtle Dermochelys coreacea in Colombia, where F. solani and F. oxysporum were identified by phylogenetic analyzes; these fungi were possibly affecting the phenotype of the hatchling (body size). The first way of contamination of the eggs by Fusarium species probably occur through the secretion present in the oviduct, as suggested by Phillot et al (2002), likewise it might be the reason for fungi contamination in nests of other species that belong to Cheloniidae family, since several species of fungi have been isolated from the cloaca of females during breeding.…”
Section: Resultssupporting
confidence: 55%
“…Relocation of sea turtle eggs as a management strategy used to increase hatchling production and enhance population recovery is ubiquitous worldwide (Chacón‐Chaverri & Eckert, ; Formia, Tiwari, Fretey, & Billes, ; García, Ceballos, & Adaya, ; Naro‐Maciel, Mrosovsky, & Marcovaldi, ; Patino‐Martinez, Marco, Quinones, & Hawkes, ). By utilizing internationally recognized best practices throughout the egg relocation process (Eckert et al, ), many of the concerns about possible undesired biological outcomes (Mrosovsky, ; Pilcher & Enderby, ; Prichard, ) can be avoided or mitigated (Kornaraki, Matossian, Mazaris, Matsinos, & Margaritoulis, ; Marcovaldi & Marcovaldi, ; Patino‐Martinez, Marco, Quinones, Abella, et al, ). Because temperatures are predicted to increase substantively in Central America over a relatively short period, the influence of sea turtle egg relocation on the thermal regimes of nest environments, primary sex ratios, and hatchling fitness compared with in situ clutches is a top research priority, particularly for severely depleted populations of highly endangered species.…”
Section: Introductionmentioning
confidence: 99%
“…Given the ubiquitous use of hatcheries for incubating sea turtle eggs worldwide (e.g., Mortimer et al 1993;Marcovaldi & Marcovaldi 1999;García et al 2003;Chacón-Chaverri & Eckert 2007;Patino-Martinez et al 2012), we believe it is important for hatchery managers to recognize the potential threat that predaceous ants pose to hatchling sea turtles. Hatchery managers may be unknowingly releasing apparently healthy but stung hatchlings to the ocean, only to have the hatchlings soon die from sting-related impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sea turtles, conservationists commonly relocate complete clutches of sea turtle eggs from high-risk nesting beaches where eggs are vulnerable to human poaching, depredation by animals, and loss by tidal inundation (e.g., Mortimer et al 1993;Marcovaldi & Marcovaldi 1999;García et al 2003;Chacón-Chaverri & Eckert 2007;Patino-Martinez et al 2012). These eggs are then usually incubated at protected hatcheries to increase survival rates of eggs and hatchlings.…”
Section: Introductionmentioning
confidence: 99%